2023
DOI: 10.1007/s11145-023-10439-x
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation in collaboration: the impact of explicit instruction and collaborative writing on secondary school students’ argumentative writing

Abstract: This paper has investigated the importance of explicit instruction and collaborative writing on (a) argumentative writing performance and (b) self-efficacy for writing of secondary school students. This intervention study additionally aimed to evaluate the effectiveness of alternating between individual and collaborative writing throughout the writing process (planning collaboratively, writing individually, revising collaboratively, and rewriting individually). A cluster randomized control trial (CRT) design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Instructional strategies is another example of an approach to argumentative writing to improve students ' text comprehension (Ka-kan-dee & Kaur, 2015). Moreover Landrieu et al, (2023) found improvement after the results of the approach instructional processes and the effects of instructional strategies were evaluated individually. Some researchers found that instructional strategies affect the students' ability in writing, as it incorporates strategies for revising and planning.…”
Section: Introductionmentioning
confidence: 96%
“…Instructional strategies is another example of an approach to argumentative writing to improve students ' text comprehension (Ka-kan-dee & Kaur, 2015). Moreover Landrieu et al, (2023) found improvement after the results of the approach instructional processes and the effects of instructional strategies were evaluated individually. Some researchers found that instructional strategies affect the students' ability in writing, as it incorporates strategies for revising and planning.…”
Section: Introductionmentioning
confidence: 96%
“…A correct argument should close with a discussion or conclusion that is universal (Carugati & Perret-Clermont, 2015;Hasnunidah et al, 2019;Mercier & Sperber, 2013). Argumentation discourse needs to be adapted by students and taught explicitly through appropriate instructions, task structuring and modeling as a lesson (Landrieu et al, 2023;Manz, 2015). Scientific argumentation involves scientific reasoning in making questions based on facts (Demircioglu et al, 2022;Faize et al, 2018;Gültepe & Kılıç, 2021;Kundariati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%